PENGARUH PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA DAN JUMLAH PENDUDUK TERHADAP KESENJANGAN DISTRIBUSI PENDAPATAN DI PROVINSI JAMBI TAHUN 2018-2024 - Marta Bayu Dwi Pratama; Titin Agustin Nengsih; Nurfitri Martaliah (Nusantara Hasana Journal, 2026)
The income distribution gap is one of the significant development challenges, even though economic growth and HDI show an increasing trend every year. This study aims to analyze the influence of economic growth, the Human Development Index (HDI), and the number of population on income distribution gaps in Jambi Province during the 2018–2024 period.  The method used was panel data regression analysis with a quantitative approach. The results show that partially, economic growth has a negative but not significant effect on income distribution gaps, which indicates that economic growth has not been enjoyed equally by all levels of society. Meanwhile, HDI and population have a significant and positive effect on income distribution gaps. The uneven increase in HDI in all regions actually widens the gap, while the increase in the number of people that is not balanced with productivity and equal distribution of resources increases inequality. Simultaneously, these three variables have a significant effect on income distribution gaps, as evidenced by the results of the F test.